Improvement of properties, and water and clay movement in vertisol-amended sand columns - Lima, José Maria de; Anderson, Sharon Jill; Pierce, Francis John; Curi, Nilton (Pesquisa Agropecuaria Brasileira, 1998)
Clay amendments may improve agricultural productivity of sandy soils by increasing nutrient- and water-holding capacities. The objective of this research was to determine the effect of Vertisol amendments on infiltration rate, available water capacity, cation exchange capacity, and clay and carbon migration in sandy soil columns. Acid-washed quartz sand was packed into PVC columns and covered with 10 cm of a Vertisol-sand mixture that contained 50, 100, 200, or 400 g kg-1 of the Ap horizon of a Vertisol (fine, montmorillonitic, thermic Typic Chromoxererts). Water was applied every other day. Leachate volume and dissolved organic carbon were measured biweekly. After 10 weeks, columns were sectioned into four layers, and chemical and physical properties were measured in each layer. Water retention, available water capacity, and cation exchange capacity increased with increasing Vertisol content. Dissolved organic C in column leachates also increased with increasing Vertisol concentration and decreased with time. The 400 g kg-1 Vertisol mixture had extremely low infiltration rate, possibly because of surface crusting. The results of this study suggest that the 200 g kg-1 Vertisol mixture had the overall physical and chemical properties most conductive to improved agricultural productivity with reasonable infiltration rate.